On the Tension Between the Elemental Nature and the Ethical Other in Levinas’s Thought: An Interpretation Conducted with the Body as a Clue - Kai Qi; Guangyao Wang (Religions)
The article discusses the irreducible tension between the elemental nature and the ethical Other in Levinas’s philosophy. Firstly, the article indicates that Levinas, as a phenomenologist, uncovers that the relationship between humans and nature is primarily characterized by sensitive enjoyment, where the sensitive body bathes and immerses itself in the elemental nature. Secondly, the paper reveals how Levinas, as both a disciple and a sharp critic of Heidegger, elucidates the anteriority of the elemental nature over the equipmental world, further illustrating how the elemental nature transforms into the world of equipment. Thirdly, the paper indicates that, as a prominent pioneer of the ethics of the Other, Levinas emphasizes the tension between nature and ethics: on one hand, the enjoyment immersing in the elemental nature leads to an egoistic way of life, while the ethical relation with the Other disrupts and breaks this egoism; on the other hand, the subject’s enjoyment and possession of nature is a necessary prerequisite for responding to the Other. Finally, the paper reveals that, when elucidating the irreducible tension between nature and ethics, Levinas, as a Jewish philosopher, is profoundly influenced by the absolute separation between the transcendence and the world that Judaism upholds.